GENDER DAN KESETARAAN DAN KEADILAN GENDER: STUDI TENTANG PENGETAHUAN DAN SIKAP MASYARAKAT BALI - Wiasti, Ni Made (Jurnal Studi Jender SRIKANDI, 2012)
Gender inequity and inequality in the community would restrict development process. Therefore, struggle toward gender equity and equality is become interesting global issue for the world and also Indonesia and Bali.The aims of this study is 1) to analyze knowledge, perception, and attitude of Balinese community toward gender concept and gender equity and equality, and 2) to know implementation of gender role in the family and community. This study is carried out in the three regencies/city in Bali, i.e. Buleleng, Tabanan and Denpasar. In each regency/city, two types of village is determined that are urban and rural. Data are collected by implementing structured interview based on questionnaire which is asked to 120 respondents and completed with in-depth interview based on interview guidance to some key respondents.The finding shows that most of respondent (68.30 %) have not known gender concept, means that only 21.70 percent stated that they already known it, and they have different understanding both about gender term and gender equity and equality. With regard to gender equity and equality, only 24.20 percent of respondent report that they have read and heard about this term. However, when it is related to gender equity and equality program, most of them (91.60 %) of respondent stated that they agree with such a program. In addition, it is also found that in the reality, almost all respondent actually have implemented job sharing between man and women flexibly, means that they swap the role of each other depend on situation and condition. This reality reflects that there is a shifting of thinking pattern of the community from rigid toward flexible division of job.Based on the findings, it can be concluded that although only small number of community member have known and understand gender concept and gender equity and equality, actually they have implemented it in their daily life. In general, community member also agree for changing their attitude toward gender role, so the condition of gender equity and equality can be achieved.
Keywords: gender, gender equity and equality